Kualitas fisik telur puyuh yang disamak Ektrak Kulit Manggis (Garcia Mangostana L) : Physical Qualities of Tanned Quail Eggs Mangosteen Skin Extract (Garcia Mangostana L) - Arisandi, Bayu; Habiburrochman, Moh (Jurnal Riset Agribisnis dan Peternakan, 2022)
Quail eggs are one of the eggs that are in great demand by consumers. Quail eggs that are stored for a long time cause depletion of the vitelia membrane so that microorganisms enter through the pores of the egg. To prevent damage to quail eggs, it is necessary to treat them by preserving tanning. The tanner used in eggs can be organic tanners that have high tannin levels. The quail eggs used amounted to 126 eggs.  Treatment of ethanol extract level of mangosteen fruit peel and long store at room temperature.  Research results The tannin content of mangosteen peel is 0.6%. The tannin content of mangosteen peel was carried out ethanol extract tannin content 1.7. The level of the extract did not differ markedly from the weight of the egg. Long shelf life of quail eggs at room temperature indicates a decrease in the weight of quail eggs. Ethanol extract of mangosteen peel for tanning has no effect on the quality of quail egg index. The egg index value of mangosteen peel extract ranges from 77.42-78.70. The shelf life treatment that tanning mangosteen peel extract does not differ from the quality of quail egg index. The result of the average value of quail egg index in weeks 0-3 ranged from 77.47-79.54. The haugh value of the ethanol extract level treatment unit ranged from 58.03 to 56.99 and there was no effect of the extract level on the HU value.  Long storage of quail eggs at room temperature shows a decreased HU value.